Earthquake resistant design for civil engineering structures, earth structures and foundations in Japan (Japan Society of Civil Engineers], 1968)
Contents: Earthquake-resisting design for earth structures and foundations. - - Earthquake resisting design features of dams in Japan. - - Earthquake resistant design for quaywalls and piers in Japan. - -Earthquake-proof measures for a water supply system. - -Earthquake engineering for bridges.